Mosquito Diversity In Livestock Cages - Herry Hermansyah; Erwin Edyansyah; Refai; Fandianta; Karneli (International Journal Scientific and Professional, 2022)
Diseases transmitted by mosquitoes are still a health problem in Indonesia, including in Banyuasin Regency, South Sumatra Province. Among the various types of mosquitoes that are vectors of the disease, some prefer animal blood. Research on the diversity of mosquitoes has been carried out in the village of Gasing. The purpose of this study was to obtain an overview of the distribution of mosquito diversity in cattle pens and goat pens. The study was conducted with free collection, namely catching mosquitoes that perch in the cage and outside the catching cage starting from 18.00 to 24.00 WIB. Distribution of the diversity of mosquitoes around the cattle pens in six locations obtained 3 genera and 8 species of mosquitoes from a total of 745 mosquitoes caught. Culex gellidus was the most common mosquito found 291 individuals (39.06%). Meanwhile, there were only 10 Aedes aegypti mosquitoes (1.34%) followed by Mansonia Indiana with 11 (1.47%). Based on the time of catching, it was found at 19.01-20.00 WIB as many as 180 fish (24.16%) which began to increase starting at 18.00 WIB. There are fewer cages in a wet environment than in a dry environment. Suggestions for starting a fire around the cage need to be continued and try to keep the cage dry.